In Vitro Hemodynamic Evaluation of ECG‐Synchronized Pulsatile Flow Using i‐Cor Pump as Short‐Term Cardiac Assist Device for Neonatal and Pediatric Population. Issue 8 (22nd April 2018) - Force, Madison; Moroi, Morgan; Wang, Shigang; Kunselman, Allen R.; Ündar, Akif
Abstract: The objective of this study was to assess the hemodynamic properties of the i‐cor ECG‐synchronized cardiac assist system for off‐label use as a short‐term cardiac assist device for neonatal and pediatric patients and compare nonpulsatile to pulsatile flow with different amplitudes. The circuit consisted of the i‐cor diagonal pump with 3 feet of ¼ inch arterial and venous tubing and a soft‐shell reservoir, primed with lactated Ringer's solution and human packed red blood cells (hematocrit 42%). Trials were conducted with three different sets of cannulas (8‐Fr arterial 10‐Fr venous, 10‐Fr arterial 12 Fr‐venous, and 12‐Fr arterial 14‐Fr venous) with increasing flow rates at varying pseudo‐patient pressures (40, 60, 80, and 100 mm Hg) and under nonpulsatile mode and pulsatile mode with pulsatile amplitudes 2000, 2500, and 3000 rpm at 36°C. Pressure and flow waveforms were recorded using a custom‐made data acquisition device for each trial. Energy equivalent pressure (EEP) was higher than mean pressure under pulsatile mode, and increased with increasing pseudo‐patient's pressure and flow rate while EEP was the same as the mean pressure under nonpulsatile mode. Total hemodynamic energy (THE) levels increased with pressure and pulsatile amplitude and slightly decreased with increasing flow rate. The percent THE lost throughout the circuit increased with flow rate and pulsatile amplitude and decreased with pseudo‐patient's pressure. SHE levels also increased with pseudo‐patient pressure and pulsatile amplitude and decreased with increasing flow rate. The i‐cor diagonal pump can be used as a short term cardiac assist device for neonatal and pediatric patients and is able to provide nonpulsatile as well as pulsatile flow. Compared with nonpulsatile flow, pulsatile flow can generate and deliver more hemodynamic energy to the patients.